Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2025)
:Table of Content• A proposed model for evaluating the organization and management of time among farmers  in applying agricultural practices / Nineveh Governorate (Literature review study)Asst-Prof. Asmaa Zuhair Younis, Lecturer. Anhar Mohammed Ali Hasan ,Asst- lecturer. Mohammed Ahmed Mahal• Effect of adding sodium lactate and acetic acid on on Verocytotoxin-producing Escherichia coli (VTEC) in red and white meatDr. Ammar Haji Al-Ali, Prof. Abdulaziz Arwaneh ,Dr. Ghiath Suleiman• Overview on Quail Management, Production and Its Physiological Performance (Article Review)Lecturer \ Khalid H. Mustafa Al-Sofee, Asst-Prof. Anwar M. Y. Al-Hamed, Prof. Abdullah F. Abdul-Majeed, Asst-Prof. Mohammad A. E. H. Osman• The Effect of Castration on Feedlot Performance and Non-Carcass Components of Young Male Sudanese Nubian GoatsMs. Manal Yassin Mohamed , Co-Prof. Yagoub Magboul Yagoub , Prof. Salih Ahmed Babiker
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences